Gamma-Nonalactone in Beer: Biosynthesis by Yeast - Garbe, Leif-Alexander (BrewingScience, 2008)
Gamma-Nonalactone is known as an aroma active and chiral compound in beer and other fermented products. Labeling experiments with tetra deuterated (9,10,12,13-2H4)-linoleic acid, single deuterated 13- and 9- hydroxyoctadecadienoic acids (HODE) and its corresponding oxygen-18 labeled oxidation product [18O1]- 13- and 9- HODE elucidated two different biosynthetic routes from linoleic oxidation products (HODE) to gamma-nonalactone in brewers yeast Saccharomyces cerevisiae and a model yeast Sporobolomyces odorus. I)13-Peroxidation of linoleic acid into 13-HODE in barley or during malting and beta-oxidation followed by one alpha-oxidation type step finally resulting in gamma-nonalactone with (S)-stereospecificity ( (S) 60 % e.e.). II)9-Peroxidation of linoleic acid into 9-HODE in barley or during malting and Baeyer-Villiger type oxidation resulting in 2E,4E-nonadien-1-ol and azelaic acid. 2E,4E-nonadien-1-ol was further transformed to gamma-nonalactone with (R)-stereo-specificity( (R) 46 % e.e.).